State of the field: Data and metrics for geographic analyses of entrepreneurial ecosystems. Issue 9 (27th July 2018) - Credit, Kevin; Mack, Elizabeth A.; Mayer, Heike
Abstract: Despite burgeoning interest in entrepreneurial ecosystems, there is little information on metrics for studying the actors and interconnections within these systems. The increasing availability of data and metrics for characterizing entrepreneurial activity in recent years provide opportunities for analyzing EE in more holistic ways. A critical first step in advancing work on this topic, however, is to critically review the use and limitations of currently available data with a focus on the very recent ecosystems literature, as well as constituent topics such as entrepreneurial heritage and spinoffs, entrepreneurial culture, and studies of emerging ecosystems in peripheral regions. In this review, the problems and prospects of available data are discussed, particularly the spatial scales (national or subnational) at which they are available. The paper closes with a critical discussion of the data needed to move the field forward in the four ecosystem‐related topical areas and answer important questions related to the nuanced geographies of EE at the subnational level. This discussion suggests present gaps may be related to a poverty of data‐sharing efforts rather than a poverty of available data.